Antecedents and outcomes of job satisfaction among royal Malaysian police (RMP) officers : A study at contingent police involved with the national key result areas (NKRA) programs / Mazlan Ismail - Mazlan, Ismail (2012)
The purpose of this study is to identify the major determinants of job satisfaction among Royal Malaysia Police (RMP) officers, by emphasizing on the environmental and demographic factors and also adding new constructs, which is implementation Community Policing (COP)/NKRA programs. Data was collected through self-administered survey questionnaires in office settings. The number of participants who returned the survey questionnaires was 452. Four measures were used: Environmental variables instrument adopted from Dubai Job Satisfaction Scale (DJSS) (Abdulla, 2009), Implementation of NKRA programs adopted from Ercikti (2008), General Job Satisfaction instrument adopted from various established studies and Job Performance instrument adopted from Goodman and Svyantek’s (1999). Data analysis started with evaluating data normality and psychometric integrity of the instruments using exploratory factor analyses. Several statistical analyses were employed to assess the hypotheses. Analyses include t-tests, ANOVA analysis, bivariate correlation analysis, and stepwise multiple regression analysis. The results of this study indicate that police officers for those who are working under Kuala Lumpur Contingent Police administrations were generally least satisfied with their jobs since 38.3% indicate low level of job satisfaction. It was further determined that the work environment is a better predictor of job satisfaction than demographic variables and the results of this study support the conclusions of previous research that demographic factors are of little value to understanding job satisfaction. Also, this study revealed that implementation of COP/NKRA programs also play an important factor that influences the level of employees’ job satisfaction may lead to job enrichment and greater job enjoyment for police officers. Moreover, demographic, environmental and NKRA variables explained 48.4% of the variance in general job satisfaction among police officers. Finally, the major determinants of job satisfaction were identified as (in order of importance): performance appraisal, salary and incentives, professional development, promotion opportunity, relationship with co-workers, communication, and nature of work. Implications for practice and future research are discussed.